Identifikasi Nilai Penting Masjid Agung Bente di Desa Ollo Selatan Kecamatan Kaledupa Kabupaten Wakatobi - Amaluddin Sope; sitti kasmiati (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2017)
Cultural resources are the regional assets that have important value that is full of history behind its existence. This includes the Great Mosque of Bente in Kaledupa which is a result of the idea of human supporters of the area. The important value of cultural resources is not only useful and beneficial for archaeology itself, but if properly managed and developed will give wider use and benefit and can be felt by all elements of society. The purpose of this study is to identify and determine the important values of the Great Mosque of Bente. In the achievement is used approach Cultural Resource Management (Cultural Resource Management) by way of collecting literature study data, direct observation in the field and subsequent interviews to speakers especially associated with the Great Mosque of Bente. Based on the results of the research, it is known that the link age of the Great Mosque of Bente with the traces of various events in Kaledupa duringthe Sultanate of Buton and Barata Kaledupa era make the Great Mosque of Bentepossess a vital importance in terms of important values of history, science,education, religion and culture significance. The importance of the Great Mosque of Bente must be maintained and for the common good in the present time and for the benefit of the next generation.